1998
DOI: 10.1038/sj.bmt.1701102
|View full text |Cite
|
Sign up to set email alerts
|

Autologous peripheral blood stem cell transplantation (PBSCT) mobilized with G-CSF in AML in first complete remission. Role of intensification therapy in outcome

Abstract: Summary:The use of peripheral blood stem cells (PBSC) in autolog- In order to determine if peripheral blood stem cells ous transplantation (PBSCT) has demonstrated advantages (PBSC) collected after priming with G-CSF in AML inover the use of marrow (ABMT) in several hematological first complete remission (CR) can be used for autologmalignancies and solid tumors. 1,2 In fact, a faster hematopoous transplantation and to evaluate the efficacy of early ietic reconstitution in PBSCT, resulting in lower infectious i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 2 publications
1
20
0
Order By: Relevance
“…26 The therapy of acute leukemias using myeloablative therapy followed by PBSC autotransplant has been recently introduced and studies are ongoing. 5,27 We treated two patients with leukemia and our experience confirms feasibility and the lack of procedure-related problems.…”
Section: Clinical Side-effects Of Pbsc Autotransplantmentioning
confidence: 56%
See 1 more Smart Citation
“…26 The therapy of acute leukemias using myeloablative therapy followed by PBSC autotransplant has been recently introduced and studies are ongoing. 5,27 We treated two patients with leukemia and our experience confirms feasibility and the lack of procedure-related problems.…”
Section: Clinical Side-effects Of Pbsc Autotransplantmentioning
confidence: 56%
“…[1][2][3][4][5][6][7] Nevertheless most reports focus on patients younger than 60 years due to higher procedurerelated risk in older patients. [6][7][8] Few reports concerning the use of high-dose therapy and autologous bone marrow 6,8 or peripheral stem cell transplantation 9,10 in the elderly are available, although growing interest in treating older patients has been shown.…”
mentioning
confidence: 99%
“…As regards CFU-GM, threshold values have ranged between Ͼ5-10 ϫ 10 4 /kg 25 and Ͼ50 CFU-GM ϫ 10 4 /kg 23 whereas other authors have failed to find an influence of this variable on the rate of engraftment. 27 In respect to the CD34 + cell dose, Demirer et al 24 and Martin et al 26 reported that patients transplanted with Ͼ2.5 ϫ CD34 + 10 6 /kg had a faster recovery of platelet counts, and in a co-operative study, patients transplanted with Ͼ12 ϫ 10 6 /kg CD34 + cells had a more rapid neutrophil and platelet recovery as compared with those receiving Ͻ3 ϫ 10 6 /kg. 27 Lastly, in a recently published report by the Bordeaux group, the number of CD34 + cells, but not the number of CFU-GM infused, showed a significant influence on the speed of engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…1 In studies of patients with AML, very few reports have evaluated the influence of the infused progenitor cell dose on engraftment, and those published included only a low number of patients. 5,[23][24][25][26][27] Thus, the minimum or optimal dose to be infused in this disease has not yet been defined. As regards CFU-GM, threshold values have ranged between Ͼ5-10 ϫ 10 4 /kg 25 and Ͼ50 CFU-GM ϫ 10 4 /kg 23 whereas other authors have failed to find an influence of this variable on the rate of engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Thus, intensification of induction/ consolidation chemotherapy, mainly based on high-dose cytarabine, has been suggested to improve in vivo purging prior to auto-SCT. [9][10][11] Combination chemotherapy regimens based on fludarabine and high-dose cytarabine, such as FLAG or FLAN, are known to be effective in myeloproliferative disorders. [12][13][14] Reinforced chemotherapy mainly based on a double high-dose consolidation regimen is a new way to enhance in vivo purging prior to auto-SCT and has not been previously reported.…”
mentioning
confidence: 99%